Motor clubs in the public arena: The Argentine Automobile Club, the Argentine Touring Club and the construction of a National Roads System (1910-43) - Piglia, Melina (2015)
The rapid spread of the automobile in the early twentieth century posed both challenges and promises to nation states. Before automobility became the object of public policies, this new mobility technology had to be socially perceived and constructed as belonging to the public sphere. Motorist associations played a decisive role in this process. This paper focuses on the Argentine Automobile Club (ACA) and the Argentine Touring Club (TCA), the two principal automobile clubs in the country and the largest ones in Latin America during the first half of the twentieth century. It argues that the ACA and TCA had a decisive influence during the 1920s in diagnosing and listing possible solutions to road and tourism challenges, and providing reference points for most of the road and tourism policies in the following decades. At the same time, both clubs actively helped to create a national network of roads through their participation in the planning agencies and made the new roadways accessible by signposting them and by providing petrol stations. Not least they formed and spread the new practices of road culture and automobility and, by organising sporting events, tours and rally drives and printing travel guides and maps, they contributed to the symbolic construction of the roads.